Kinetic Study of Cr(III) and Cr(VI) Biosorption Using Rosa damascena Phytomass: A Rose Waste Biomass - Jamshaid Iqbal, M.; Cecil, Farhan; Ahmad, Khalil; Iqbal, Munawar; Mustaq, M.; Naeem, M.A.; Bukhari, T.H. (Asian Journal of Chemistry, 2012)
In present study, Cr(III) and Cr(VI) sorption capacity of Rosa damascena phytomass from aqueous solution was evaluated. The R. damascena phytomass biosorption revealed that smaller biosorbent size (< 0.4 g), dose (< 0.1 g), pH (2 and 5 for Cr VI and III) and 100 mg L-1 initial metal concentration were more suitable for better biosorption from aqueous medium. The Langmuir isotherm model and pseudo second order kinetic model fitted well to the data of Cr(III) and Cr(VI) biosorption. The negative value of Gibbs free energy (DGº) indicated the spontaneous absorption process. The R. damascena biomass pre-treatment enhanced biosorption considerably and it is concluded that the R. damascena biomass (waste material) might be used for biosorption of Cr(III) and Cr(VI) from aqueous solution.